Gender Smart Policymaking in Ghana - World Bank Group (World Bank, Washington, DC, 2015)
Women in Ghana face many of the same constraints to economic participation that affect millions of women across the continent. These constraints include large gender gaps in access to productive inputs, time spent on domestic chores, and the quality and number of jobs and other opportunities available. This is harmful to not only women but also families, communities, and economies.